2009
DOI: 10.1161/hypertensionaha.108.124115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Agonistic Autoantibodies Against the Angiotensin II Type 1 Receptor and Soluble fms-Like Tyrosine Kinase 1 in a Gestational Age–Matched Case Study

Abstract: Abstract-We showed earlier that activating autoantibodies against the angiotensin II type 1 (AT 1 ) receptor (AT1-AA) circulate in preeclamptic women. They may be involved in the pathogenesis of preeclampsia. Protein alignment suggests that the binding site for AT1-AAs is highly homologous to the capsid protein VP2 of parvovirus B19. We performed a prospective, nested, case-control study of 30 gestational age-matched women with preeclampsia and 30 normotensive pregnant women. We measured AT1-AA, soluble fms-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 51 publications
6
59
1
2
Order By: Relevance
“…5,6,11 Although the antibodies against this ECL2 sequence discovered thus far show agonistic effects, [12][13][14][15][16] we cannot rule out the possible existence of blocking antibodies to that region. Many researchers have attempted to identify a G protein coupling receptor antibody that can act as an agonist or an antagonist.…”
Section: Discussionmentioning
confidence: 87%
“…5,6,11 Although the antibodies against this ECL2 sequence discovered thus far show agonistic effects, [12][13][14][15][16] we cannot rule out the possible existence of blocking antibodies to that region. Many researchers have attempted to identify a G protein coupling receptor antibody that can act as an agonist or an antagonist.…”
Section: Discussionmentioning
confidence: 87%
“…Since Wallukat et al 7 described the presence of AT 1 -AA in PE patients, many features of the disease has been explained by the ability of this autoantibodies to bind to and to activate the angiotensin receptor on a variety of cells. [29][30][31][32][33] However, despite much information concerning the presence of autoantibodies in PE patients, no attention has so far been focused on the cells producing them. We focused our attention on the B-1a B cells.…”
Section: Discussionmentioning
confidence: 99%
“…65 In a case-control study, we found that such antibodies were relatively common in normal pregnancy controls and not present in a substantial minority of cases. 66 Cross-reactivity with parvovirus B19 VP2 protein was demonstrated although serological evidence of previous parvovirus infection was not more common in pre-eclampsia cases. Th17 activity predisposes to autoimmunity.…”
Section: Pre-eclampsia and Autoantibodiesmentioning
confidence: 96%